1998
DOI: 10.1175/1520-0493(1998)126<3102:romltc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Multiple-Level Tropospheric Circulations in Forcing ENSO Winter Precipitation Anomalies

Abstract: Regionally organized winter (DJF) precipitation anomalies over North America are presented in association with cold and warm phases of the ~ Nifio-Southern Oscillation. Variations in low-level flow from moisture sources aDd in upper-level dynamic properties are diagnosed for eKb anomalous precipitation region using DJF composites of upper-and lower-tropospheric winds. sea level pressure. divergence, and vorticity advection. Variance analysis determines which precipitation and circulation patterns are robust an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
5
33
0
Order By: Relevance
“…This study complements earlier research into atmospheric circulation and winter climate over North America (Barton and Ramirez, 2004;Cayan, 1996;Coleman and Rogers, 2003;Serreze et al, 1998;Smith et al, 1998). A new association is suggested between preceding season PDO and winter SWE over the eastern portion of the continent.…”
Section: Resultssupporting
confidence: 78%
“…This study complements earlier research into atmospheric circulation and winter climate over North America (Barton and Ramirez, 2004;Cayan, 1996;Coleman and Rogers, 2003;Serreze et al, 1998;Smith et al, 1998). A new association is suggested between preceding season PDO and winter SWE over the eastern portion of the continent.…”
Section: Resultssupporting
confidence: 78%
“…Their results are consistent with others who found similar relationships between ENSO phase and storm activity in the region of the SOC track (Noel and Changnon 1998;Hirsch et al 2001;Schubert et al 2005). The ENSO teleconnection with storminess in the eastern United States occurs via strengthening of the southern branch of the jet stream over North America (Smith et al 1998) and an increase in sea surface temperature in the GOM and southeastern U.S. coastal regions (DeGaetano et al 2002). Despite the advantages of modern meteorological products, they are not suitable for analyses of multidecadal variability in storminess, because they are limited temporally to the second half of the twentieth century.…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies have shown that the frequency and intensity of tropical cyclones and winter cold fronts in this area are affected by climate variability. For example, Eichler and Higgins (2006) found Gulf of Mexico cyclogenesis occurred more often during the warm El Niño Southern Oscillation (ENSO) phase, because of strengthening of the southern branch of the jet stream over North America (Smith et al 1998) and increased sea surface temperature in the Gulf of Mexico (DeGaetano et al 2002). Thompson et al (2013) corroborated the previous findings and identified a multidecadal increase in storm frequency from early to late twentieth century along the Gulf of Mexico and over the southeastern coast.…”
Section: Introductionsupporting
confidence: 59%